Detekcija nevidnih interferenčnih slik z Michelsonovim interferometrom - Verovnik, Ivo (Obzornik za matematiko in fiziko, 2010)
In experiments with Michelson interferometer the interference pattern can be seen at full contrast in case of equidistant position of both the mirrors. When the difference of the lengths of both arms increase, the contrast fades away due to incoherence of light and the pattern diminishes completely when the difference is substantially bigger than the coherence length of the light. When using fast enough detectors, the distance between invisible interference fringes can be detected even at large difference of the length of the interferometer arms. The experiment, which authors carried out, and the didactical models and tools to explain the phenomenon are presented.
Keywords: fizika; interferenca